Doing applied linguistics : a guide for students - Groom, Nicholas (Routledge, 2011)
Doing Applied Linguistics provides a concise, lively and accessible introduction to the field of applied linguistics for readers who have little or no prior knowledge of the subject. The book explores the basics of the field then goes on to examine in more depth what applied linguists actually do, and the types of research methods that are most frequently used in the field. By reading this book students will find the answers to four sets of basic questions: